Diversity and Conservation of Cave-Roosting Bats in Central Ghana. (July 2021) - Nkrumah, Evans Ewald; Baldwin, Heather Joan; Badu, Ebenezer Kofi; Anti, Priscilla; Vallo, Peter; Klose, Stefan; Kalko, Elisabeth Klara Viktoria; Oppong, Samuel Kingsley; Tschapka, Marco
Background: Ghana is one of the six bat diversity hotspots on the African continent, yet its caves have not been fully explored for the bats they host. Research Aims: We aimed to assess the species composition and diversity of five caves in central Ghana and identified those needing immediate conservation attention. Methods: Using mist-nets, we captured bats over 102 full nights between October 2010 and July 2012 from the Upper Guinean forest and Savannah regions in central Ghana. Results: A total of 10, 226 bats belonging to nine species were recorded. PERMANOVA suggested significant variation in species composition among the caves. A SIMPER analysis revealed Coleura afra and Hipposideros jonesi to be the main discriminating species between caves, with a dominance of Hipposideros cf. ruber in all caves. The Bat Cave Vulnerability Index (BCVI) revealed Mframabuom cave from the Upper Guinean forest region as a high priority cave hosting threatened species, yet highly disturbed. The remaining caves were identified as medium priority caves. Conclusion: The results of the study suggest the need for further research and an immediate conservation strategy as essential for approaching national conservation goals.